2017
DOI: 10.1111/jopy.12339
|View full text |Cite
|
Sign up to set email alerts
|

Extraversion and life satisfaction: A cross‐cultural examination of student and nationally representative samples

Abstract: The findings attest to the moderating role of culture on Extraversion and life satisfaction and the importance of controlling for shared method variance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 58 publications
2
45
0
Order By: Relevance
“…These findings are in line with other studies, which also showed that extraversion was the strongest predictor of life satisfaction (Joshanloo and Afshari 2011;Schimmack et al 2004). There might be crosscultural differences, however, as shown in the recent study by Kim et al (2018), whose results are in line with ours. Emotional stability is a salient predictor of life satisfaction and happiness, as shown in a meta-analysis of the relationships between 137 distinct personality constructs and subjective well-being (DeNeve and Cooper 1998).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in line with other studies, which also showed that extraversion was the strongest predictor of life satisfaction (Joshanloo and Afshari 2011;Schimmack et al 2004). There might be crosscultural differences, however, as shown in the recent study by Kim et al (2018), whose results are in line with ours. Emotional stability is a salient predictor of life satisfaction and happiness, as shown in a meta-analysis of the relationships between 137 distinct personality constructs and subjective well-being (DeNeve and Cooper 1998).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, other correlates of extraversion have been evidenced to be less culturally invariant. For instance, the association between extraversion and life satisfaction may be present only in North America (Kim et al, 2017). Of course, a wider range of cultures, and non-WEIRD cultures in particular, should be considered in order to more rigorously test this cultural invariance in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this idea, recent results have suggested that the widely reported association between extraversion and life satisfaction is culture-sensitive. This association is strong only in North America and is weaker or non-significant in other cultures (Japan, Germany, and United Kingdom: Kim, Schimmack, Oishi, & Tsutsui, 2017). Thus, it is possible that there is also cultural sensitivity in the association between extraversion and popularity, especially since many of the previous studies have used North American samples (e.g., DesJardins et al, 2015;Jensen-Campbell et al, 2002;Jensen-Campbell & Malcolm, 2007).…”
Section: Is Extraversion Associated With Popularity In a Less Talkorimentioning
confidence: 93%
“…Cultural influences on life satisfaction have also attracted broad interest, particularly focusing on the differences between collectivistic and individualistic cultures (e.g. Kim et al 2018;Park et al 2004;Schimmack et al 2002;Tov and Diener 2013), and highlighting differences in levels of life satisfaction across nations (Diener and Suh 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also focused on individual differences in life satisfaction and SWB; for example, the association between overall life satisfaction and personality (e.g. Fowler et al 2018;Kim et al 2018;Zalewska et al 2018), as well as the association between specific variables of life satisfaction (e.g. family, leisure, income) and overall life satisfaction (e.g.…”
Section: Introductionmentioning
confidence: 99%